(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
We begin these lines by stating without a doubt that the issue discussed here is the richest, institutionally speaking, of the last decade due to the path it has taken, not only because of its controversial content but also because of the way it ended with a very solvent constitutional disavowal of the other branches of government. a very solvent constitutional disasne of the Supreme Court of Justice of the Nation towards the other branches of government. But perhaps the most remarkable thing is that it was without any stridency and with the wisdom that sometimes abounds in simple words and even if it was more for simplicity than for wisdom this does not detract one iota of institutional and constitutional authority to such decision.The issue and also the discussion began long before the congress sanctioned the law of reforms to the council of the magistrature and then the Court in turn and turn declared the unconstitutionality of its most radical articles. This begins with the famous announcement of “Democratization of Justice” enunciated by the President of the Nation Cristina Fernández de Kirchner which she herself then institutionalized in her speech to the Legislative Assembly on March 1 on the occasion of the beginning of the period of ordinary sessions of the national legislative branch and which she finally formalized during the first days of April 2013.